Information System for Early Detection of Dental and Mouth Diseases in Pregnant Women - Sariyem Sariyem; Irmanita Wiradona; Sadimin Sadimin (Jurnal Kesehatan Gigi, 2021)
AbstractProblems with dental and oral health are experienced by pregnant women, including 30-100% of pregnant women experiencing gingivitis. Dental and oral health checks in pregnant women include a dental and oral health assessment card that contains the habits of pregnant women that can affect the risk of dental and oral diseases. The use of the card is not maximal and has not been widely used, so that dental and oral diseases in pregnant women are still high and cannot be detected properly.Objective: To produce innovations in the effort of early detection of risk information for dental and oral diseases based on information to support dental and oral health of pregnant womenMethod: The research method used in this study is the Research and Development method or research planning and development. With a sample of 20 consisting of 5 dentists, 5 dental nurses, 5 midwives, and 5 pregnant women. The main field test uses quasi-experimental post-test only control group design. The research instrument used was a questionnaire to assess the feasibility of media and questionnaires to test testimonials using the chi-square test.Results: there is a significant value in the test testimony of the application of early detection of dental and oral diseases in pregnant women seen with a p-value of 0.05, which means the application of early detection of dental and oral diseases as a medium of information that is easily acceptedConclusion: the application of early detection of dental and oral diseases in pregnant women is more effective than the dental health examination card in pregnant women